Pathological fracture of the mandible associated to osteoradionecrosis: A case report - Ronal; Sylviana Melita; Syamsuddin Endang (Journal of Dentomaxillofacial Science, 2020)
Objective: Osteoradionecrosis (ORN) is a severe and devastating late complication of radiotherapy in patients with head and neck cancer, especially in the mandible. Methods: We report a case of a 47-year-old woman who suffering from osteoradionecrosis and bone exposure 5 yearsafter irradiation therapy for Squamous Cell Carcinoma (SCC) of the tounge. Segmented resection of the mandible was performed followed with reconstruction using plate. Results: ORN can cause pathological fracture of the mandible and should be treat with surgical approach Conclusion: ORN affects the mandible more often than the maxilla or any other bones of head and neck, since it has high density and low blood vasculature so can cause pathological fracture of the mandible. Preventive measures must be evaluated to reducing the risk or severity of ORN